Correction: Controlled p-type substitutional doping in large-area monolayer WSe2 crystals grown by chemical vapor deposition. Issue 1 (11th December 2018) - Pandey, Sushil Kumar; Alsalman, Hussain; Azadani, Javad G.; Izquierdo, Nezhueyotl; Low, Tony; Campbell, Stephen A.
Abstract : Correction for 'Controlled p-type substitutional doping in large-area monolayer WSe2 crystals grown by chemical vapor deposition' by Stephen A. Campbell et al., Nanoscale, 2018, 10, 21374–21385.